Effects of Local Vibration With Different Intermittent Durations on Skin Blood Flow Responses in Diabetic People - Ren, Weiyan; Pu, Fang; Luan, Huiqin; Duan, Yijie; Su, Honglun; Fan, Yubo; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2019)
Objective: Poor blood flow supply is an important pathological factor that leads to the development and deterioration of diabetic foot ulcers. This study aims to investigate the acute effects of local vibration with varying intermittent durations on the plantar skin blood flow (SBF) response in diabetic and healthy subjects. Methods: Eleven diabetic patients (7 males, 4 females) and 15 healthy adults (6 males, 9 females) participated in this experiment and accepted three tests. Local continuous vibration (LCV) and two levels of local intermittent vibration (LIV1 and LIV2) were randomly applied to the middle metatarsal head of each subject's right foot in each test. The SBF was measured prior to intervention (Baseline), during Vibration and during the Recovery Stage for each test. The mean SBF in each stage, the change percentages and change rates of SBF in Vibration and Recovery stage among three tests were compared and analyzed for both diabetic and healthy subjects. Results: For diabetic subjects, the SBF was significantly increased in both Vibration and Recovery Stage with local intermittent vibrations (LIV1 and LIV2), but not with LCV. However, there was no significant difference in change percentage and change rate of SBF in diabetic subjects across the three tests. For healthy subjects, all vibration interventions significantly increased the SBF in the Vibration Stage and in the first 1.5 min of the Recovery Stage. Also, the change rate of SBF during the Vibration stage in LIV1 test was significantly greater than that in LIV2 test for healthy subjects. Moreover, change percentage of SBF in Vibration stage of LIV1 test and in some periods of Recovery stages of LIV1 and LIV2 tests for diabetic subjects were lower than for healthy subjects; the absolute change rate of SBF in LIV1 test for diabetic subjects was also lower than for healthy subjects. Conclusion: These findings suggest that both LIV1 and LIV2 may effectively improve SBF in the feet of diabetic people, but LCV may not achieve the same level of vasodilatation. The diabetic subjects were also found to have a lower SBF response to applied vibration than the healthy subjects.